2015
DOI: 10.12705/646.4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetics, morphology and a revised classification of the complex genus Saxifraga (Saxifragaceae)

Abstract: Saxifraga, the most species‐rich and taxonomically complex genus of Saxifragaceae, is a characteristic component of temperate to polar climatic zones and of montane to alpine vegetation belts in mountain ranges of the Northern Hemisphere. The genus encompasses more than 440 species, which display notable diversity in growth form, vegetative and reproductive characters, as well as in micromorphology of pollen grains and seeds. Using a large taxon set including representatives attributed to nearly all recognised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
120
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 65 publications
(131 citation statements)
references
References 68 publications
(100 reference statements)
10
120
1
Order By: Relevance
“…More recently, Tkach et al. () found S. terektensis , S. cespitosa ssp. monticola and S. hypnoides to be closely related to S. rosacea .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Tkach et al. () found S. terektensis , S. cespitosa ssp. monticola and S. hypnoides to be closely related to S. rosacea .…”
Section: Methodsmentioning
confidence: 99%
“…Saxifraga, Vargas (2000) identified a polytomic subclade consisting of S. rosacea, S. hartii, S. graeca, S. granulata and S. cespitosa. More recently, Tkach et al (2015) found S. terektensis, S. cespitosa ssp. monticola and S. hypnoides to be closely related to S. rosacea.…”
Section: Study Speciesmentioning
confidence: 99%
“…The genus Saxifraga L. (Saxifragaceae) consists of approximately 500 species that are mainly distributed in the mountainous regions of Europe and Asia (Pan et al., ; Gao et al., ; Tkach et al., ), including the Qinghai–Tibetan Plateau (QTP) and Hengduan Mountains region (HDM), which is a biodiversity hotspot of Saxifraga (Pan et al., ). Saxifraga sinomontana J. T. Pan & Gornall is a widespread perennial herb in the QTP and its peripheral regions.…”
mentioning
confidence: 99%
“…However, S. sinomontana is an extraordinarily variable species in morphology, as described in the Flora of China (Pan et al., ), as well as according to our long‐term field surveys, which have demonstrated that gradations in traits are common in the species (e.g., plant height, number of flowers). Saxifraga sinomontana has been the focus of recent systematics research (Gao et al., ; Tkach et al., ), and Li et al. () revealed that this species possesses a high level of genetic diversity, which may be the result of Quaternary climatic oscillations.…”
mentioning
confidence: 99%
“…Saxifraga L. is the largest genus in the Saxifragaceae family, with more than 440 species widely distributed throughout the Northern Hemisphere (Tkach et al., ). A recent phylogenetic study divided this genus into 13 sections and nine subsections, with section Irregulares Haw., a well characterized group with zygomorphic flowers, as the earliest diverged lineage (Tkach et al., ). This section comprises 15–20 species growing in moist temperate areas of East Asia, whereas most other sections of Saxifraga are widely distributed in boreal and/or alpine areas (Pan, ).…”
mentioning
confidence: 99%